1997
DOI: 10.1152/ajpheart.1997.273.2.h593
|View full text |Cite
|
Sign up to set email alerts
|

Role of the renin-angiotensin system in cardiac hypertrophy induced in rats by hyperthyroidism

Abstract: This study was conducted to examine whether the renin-angiotensin system contributes to hyperthyroidism-induced cardiac hypertrophy without involving the sympathetic nervous system. Sprague-Dawley rats were divided into control-innervated, control-denervated, hyperthyroid-innervated, and hyperthyroid-denervated groups using intraperitoneal injections of thyroxine and 6-hydroxydopamine. After 8 wk, the heart-to-body weight ratio increased in hyperthyroid groups (63%), and this increase was only partially inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
2
4

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(63 citation statements)
references
References 38 publications
1
56
2
4
Order By: Relevance
“…A growing body of evidence indicates that the renin-angiotensin system (RAS) has a critical role in the development of cardiac hypertrophy found in hyperthyroidism and the local RAS, present in the cardiomyocytes, is directly implicated in this process (Diniz et al 2009, Carneiro-Ramos et al 2010. In this sense, the contribution of the RAS in this pathological condition has been demonstrated by several studies reported in the literature, which showed that AT1R receptor blockade and angiotensin-converting enzyme inhibition attenuate or prevent the development of cardiac hypertrophy induced by THs (Kobori et al 1997, Asahi et al 2001, Basset et al 2001, Hu et al 2003, Pantos et al 2005.…”
Section: Introductionmentioning
confidence: 94%
“…A growing body of evidence indicates that the renin-angiotensin system (RAS) has a critical role in the development of cardiac hypertrophy found in hyperthyroidism and the local RAS, present in the cardiomyocytes, is directly implicated in this process (Diniz et al 2009, Carneiro-Ramos et al 2010. In this sense, the contribution of the RAS in this pathological condition has been demonstrated by several studies reported in the literature, which showed that AT1R receptor blockade and angiotensin-converting enzyme inhibition attenuate or prevent the development of cardiac hypertrophy induced by THs (Kobori et al 1997, Asahi et al 2001, Basset et al 2001, Hu et al 2003, Pantos et al 2005.…”
Section: Introductionmentioning
confidence: 94%
“…Ichihara et al (1998) found that triiodothyronine (T 3 ) administration increases renin secretion, renin content, and renin mRNA in rat juxtaglomerular cell cultures. Various authors observed this direct action in cardiac tissue from hyperthyroid rats and reported that thyroid hormones directly stimulate renin mRNA and the promoter activity of the human renin gene via thyroid hormone regulating elementdependent mechanisms (Gilbert et al 1994, Kobori et al 1997a,b, 2001). These actions of thyroid hormones on renin secretion and renin mRNA are direct and not mediated by changes in sympathetic nervous system activity (Kobori et al 1997a,b).…”
Section: Reninmentioning
confidence: 99%
“…These actions of thyroid hormones on renin secretion and renin mRNA are direct and not mediated by changes in sympathetic nervous system activity (Kobori et al 1997a,b). However, the above studies do not rule out the possibility that RAS activity modifications in thyroid Hauger-Klevene & Levin 1976, Jiménez et al 1982, Santos & Ferreira 2007 [ (Jiménez et al 1984);Y (Hauger-Klevene & Levin 1976, Jiménez et al 1982) Angiotensin-converting enzyme [ (Phillips et al 1993) Y , Jiménez et al 1990) Angiotensin II [ (Marchant et al 1993, Garcia del Río et al 1997, Kobori et al 1997a Y (Marchant et al 1993, Kobori et al 1997a New RAS components --Heart Renin Kobori et al 1997a,b, 1999 Marchant et al 1993 [ (Marchant et al 1993) Kidney Renin [ (Bouhnik et al 1981, Kobori et al 1997a,b, Klein & Ojamaa 2001)…”
Section: Reninmentioning
confidence: 99%
“…Battista (2002) Paralelamente, sabe-se que a razão dada pelo peso da placenta/peso corpóreo (PP/PC) corresponde a uma relação crítica, visto que diferentes estudos a relacionam com risco de doença cardiovascular na vida adulta (Barker et al, 1989(Barker et al, , 1990Leon et al, 1998). Neste sentido, se por um lado estudos mostram que o elevado peso da placenta pode refletir um aumento da pressão arterial em crianças (Law et al, 1991;Moore et al, 1996), por outro, achados já mostraram uma relação inversa entre esses dois parâmetros (Willians et al, 1992;Whincup et al, 1995;Taylor et al, 1997 Anjos-Ramos et al, 2006;Kobori et al, 1997Kobori et al, , 1998. Porém, a ação de tais hormônios no período fetal e as possíveis repercussões do hipertiroidismo gestacional no desenvolvimento e crescimento do coração na prole ainda permanece desconhecida.…”
Section: Hipertiroidismo Experimental: Efeitos Sobre a Proleunclassified
“…Inúmeros estudos, inclusive os de nosso grupo, têm demonstrado a participação do SRA no desenvolvimento da hipertrofia cardíaca, induzida pelo hipertiroidismo, em indivíduos adultos (Kobori et al, 1997(Kobori et al, , 1999Basset et al, 2001;Hu et al, 2003;Carneiro-Ramos et al, 2010 (Urata et al, 1990), mas a formação de Ang II independentemente da ECA já foi descrita ocorrer em corações de cachorros e hamsters (Gondo et al, 1989) através de uma enzima denominada quimase (Chy).…”
Section: Efeitos Sobre O Sra Cardíacounclassified